ABC (De)’s Stages of Relationship as Seen in Henry James’s the Portrait of A Lady - Dyah Aju Hermawati (Unipdu Jombang, 2018)
Dyah Aju Hermawatiermawati26@yahoo.comEnglish Department State Polytechnic of Jember AbstractThis article with reference to James’s novel The Portrait of a Lady (1881) tries to describe Isabel’s stages of relationship. Henry James is primarily known for series of major novels in which he portrayed the encounter of Americans with Europeans, and his plot centered on the personal relationship. Relationship is one of the most domineering and recurring motifs in the works of James. James’ main contention for personal relationship is that a relationship develops through stages of relationship. To analyze it, George Levinger’s stages of relationship theory is applied, starting from the (A) attraction stage, (B) building stage, (C) continuation stage, (D) deterioration stage and (E) ending stage. Based on the analysis,it can be described that Isabel’s relationship with Osmond develop through five stages of relationship. It is began when they are attracted each other and building a relationship, then their relationship become consolidated. When they feel that their relationship as less desirable or worthwhile and the deterioration can not be stopped, they end their relationship due to lack of love, trust and mutual understanding as the root cause for the failure of a relationship. Hence, in a relationship individuals should be aware of loving, understanding, trusting each other and caring commitment to continue and maintain a relationship for long term success.[WU1] Key Words : personal relationship, stages of relationship AbstrakArtikel tentang novel Henry James yang berjudul The Portrait of a Lady (1881) bertujuan mendeskripsikan tahapan-tahapan hubungan dari tokoh utama wanita, yaitu Isabel Archer. Henry James adalah penulis yang terkenal dengan novel-novelnya yang mendeskripsikan hubungan antara orang Amerika dengan orang Eropa, dan alur ceritanya berpusat pada hubungan antar individu. Hubungan antar individu adalah motif yang dominan pada tulisan James, terutama bahwa suatu hubungan antar individu akan berkembang melalui tahapan-tahapan hubungan.Untuk menganalisanya, diaplikasikan teori tahapan-tahapan hubungan George Levinger, mulai dari tahapan perkenalan (Attraction Stage), tahapan membangun suatu hubungan (Building Stage), tahapan melanjutkan hubungan (Continuation Stage), tahapan kemunduran hubungan (Deterioration Stage) dan tahapan akhir hubungan (Ending Stage). Berdasarkan analisa, dideskripsikan bahwa hubungan Isabel dan Osmond, berkembang melalui lima tahapan hubungan. Mulai dari tahapan perkenalan, yaitu tahap mereka pertama kali bertemu, kemudian tahapan membangun suatu hubungan yang lebih dekat, sampai berlanjut pada satu ikatan berkomitmen. Ketika mereka mulai merasakan bahwa hubungannya tidak lagi diinginkan dan mengalami kemunduran, dan hal ini tidak dapat dihentikan, maka mereka mengakhiri hubungan. Sebab utama kegagalan suatu hubungan karena kurangnya kasih sayang, kepercayaan dan pengertian. Oleh karena itu untuk menjalin suatu hubungan, antar individu harus saling mengerti dan percaya satu sama lain dan selalu memegang komitmen serta menjaga hubungan tersebut berlansung sukses.Kata-kata Kunci: hubungan antar individu,Tahapan-tahapan hubungan